Analisis Penegakan Hukum terhadap Pelanggaran Hak Desain Industri (Studi Kasus Pelanggaran Desain Industri Eco Bottle) - Novia, Elsa Ari; Kristoffel, Chesario Own; Adillah, Alya Sophia; Prayoga, Ananta Dwi; Antoni, Herli (Faculty of Law, University of Dr. Soetomo, 2023)
Similarity in bottle designs between various companies is one of the new issues that has emerged as the eco-bottle sector in Indonesia has grown. Inadequate legal protection has been provided to the owners of the eco-botol industrial design, which ought to be fiercely safeguarded, and there are no legislation that specifically address design imitation and false representation. This essay employs a comparative approach; specifically, the author contrasts Indonesia's industrial design rights laws with those in the United States, which have proven effective in protecting industrial design rights holders. Because of the importance of this comparison, industrial design rights holders should consider it before Indonesia's industrial design rights laws are finalized.